2021
DOI: 10.1097/01.asw.0000725192.98920.c4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multimedia Patient Education Intervention on Improving Self-care Knowledge and Skills in Patients with Colorectal Cancer after Enterostomy Surgery: A Pilot Study

Abstract: OBJECTIVE Colorectal cancer is most commonly treated through surgery. Self-care knowledge and skills are instrumental for disease adaptation once the patient returns home. Therefore, this study examined the effects of a multimedia patient education intervention on improving self-care knowledge and skills in patients with colorectal cancer who underwent colostomy surgery. METHODS A quasi-experimental design was adopted to measure the self-care knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
0
11
0
5
Order By: Relevance
“…Prompt followup of discharged patients has been related to reduced postoperative complications 8,9 and improved functional ability and quality of life. 10 Patients undergoing CRC surgery need continued healthcare service following discharge for symptom management 11 , skill development 12 , psychosocial support 13 , access to health care 14 , continuity of care 9 and effectiveness of healthcare services for the purpose of maintaining HRQoL and reducing postoperative complication rates.…”
Section: Introductionmentioning
confidence: 99%
“…Prompt followup of discharged patients has been related to reduced postoperative complications 8,9 and improved functional ability and quality of life. 10 Patients undergoing CRC surgery need continued healthcare service following discharge for symptom management 11 , skill development 12 , psychosocial support 13 , access to health care 14 , continuity of care 9 and effectiveness of healthcare services for the purpose of maintaining HRQoL and reducing postoperative complication rates.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with Alhawri, et al, (2020) (3) who conducted a study entitled "Knowledge, Attitude, Performance and Associated Factors towards Colostomy Care among Nurses in Public Hospitals" and found that there is a statistically significant relation between total performance and their demographic characteristics. Conversely, this result is in disagreement with Wang, et al, (2021) (18) who conducted a study entitled "Effectiveness of a Multimedia Patient Education Intervention on Improving Self-care Knowledge and Skills in Patients with Colorectal Cancer after Enterostomy Surgery" and found that there is no statistically significant relation between total performance and their demographic characteristics.…”
Section: Discussionmentioning
confidence: 85%
“…More than one third of participants had experiences less than 5 years. More than two thirds of participants (18) who conducted a study entitled "Effectiveness of a Multimedia Patient Education Intervention on Improving Self-care Knowledge and Skills in Patients with Colorectal Cancer after Enterostomy Surgery" and found that more than half of nurses were female, had technical nursing institute, and their ages from 20: 30 years. Conversely, this result is in disagreement with Bagheri, et al, (2017) (24) who conducted a study entitled "Nurses' Knowledge About Fecal Intestinal Ostomies's Care" and found that half of nurses had experiences less than 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no study in the literature has examined the effect of video-assisted CIC training on patients' practical skills, studies evaluating the validity of CIC training videos have shown that these videos can contribute to the education of patients and their compliance with catheterization [22,23]. In video-assisted trainings on other diseases, the videos provide visual and auditory learning and have a positive effect on transforming knowledge into practice and behavior by combining theory and practice [4,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%